Wrist-ankle acupuncture alleviates pain in the acute phase of herpes zoster: A randomized controlled trial - Jing Pu; Daiwen Li; Xia Luo; Juan Wang; Yanxia Li; Li Lei; Xiankun Zhao; Huan Du; Xiyue Yang; Xiaobo Du (PLoS ONE, 2025)
Alternative therapeutic strategies for herpes zoster, especially for acute phase pain relief, are still largely unexplored. This study aimed to compare the effects of wrist-ankle acupuncture combined with standard pharmacological treatment versus standard pharmacological treatment alone in relieving pain in the acute phase of herpes zoster. An open-label, randomized, controlled clinical trial was conducted, enrolling patients diagnosed with acute-phase herpes zoster with pain visual analog scale (VAS) scores greater than or equal to 2. The participants were randomly assigned to either the control group receiving standard pharmacological treatment (antiviral therapy combined with pain relievers) alone or the experimental group receiving wrist-ankle acupuncture plus standard pharmacological treatment. VAS pain scores were recorded on days 1–7 and on day 28 after treatment began. Dermatology Life Quality Index scores were assessed both during the pre-treatment phase and at hospital discharge. A total of 106 patients completed the trial protocol and were included in the analysis, with 52 and 54 patients in the control and experimental groups, respectively. The clinical cure rates of pain (the rate of complete absence of pain) in the experimental group was statistically higher than control group on days 7 after treatment began(87.04% vs 65.38%, p < 0.005). The average pain VAS scores of the experimental group were lower than the control group on days 2–6 after treatment began, and they are statistically significant (all p < 0.05). No significant difference was observed between day 7 and day 28 after treatment began (p > 0.05). The Dermatology Life Quality Index scores significantly differed at hospital discharge (p < 0.05). Side effects did not significantly differ between the two groups (all p > 0.05). Wrist-ankle acupuncture combined with standard pharmacological treatment may potentially improve the pain cure rate at 7 days post-treatment. This suggests a potential new strategy for alleviating pain in patients in the acute phase of herpes zoster. Trial registration: ChiCTR2300071795.